Pengaruh Pengembangan Karir, Kompetensi, dan Motivasi Terhadap Kinerja Karyawan Pada PT. Cubiespot Pilar Data Nusantara di Kota Pasuruan - Muhammad Khoirul Fata; Abdul Kodir Djaelani; Alfian Budi Primanto (UNIVERSITAS ISLAM MALANG, 2022)
Abstract This study aims to examine and explain the effect of career development, competence, and motivation on employee performance at PT Cubiespot Pilar Data Nusantara in Pasuruan City. This research is an associative research type with a quantitative approach. The method used is multiple linear regression. The sampling technique of this research is using purposive sampling technique. Purposive sampling is a data sampling technique based on certain considerations. If the subject is less than 100, it is better to take all of them. On the other hand, if the subject is greater than 100, it can be taken between 10-15% or 20-25%. From this explanation, the researcher took 35 samples of all respondents. To solve the problem in this study using SPSS assistance with validity test, reliability test, instrument test, multiple linear regression analysis, multicollinearity test, heteroscedasticity test, F test, and t test. The results showed that simultaneously the variables of the influence of career development, competence, and motivation had an effect on employee performance. And there is a partial influence between the variables of career development, competence, and motivation on employee performance. Keywords: Career Development, Competence, Motivation, Employee Performance